Clinical significance of chloride-to-phosphorus and chloride-to-magnesium ratios in primary hyperparathyroidism - Turan Erdoğan, Beril; Çopuroğlu, Esra; Karaahmetli, Gülsüm; Dellal Kahramanca, Fatma Dilek; Çuhacı Seyrek, Fatma Neslihan; Başer, Hüsniye; Topaloğlu, Oya; Ersoy, Reyhan; Çakır, Bekir (Journal of health sciences and medicine : (Turkey), 2025)
Aims: Primary hyperparathyroidism (PHPT), a well-recognized endocrine disorder, is subclassified into hypercalcemic and normocalcemic forms. Recent studies suggest that biochemical ratios such as the chloride-to-phosphorus (Cl/P) and chloride-to-magnesium (Cl/Mg) ratios may aid in the diagnostic evaluation and risk stratification of PHPT-related complications. This study aimed to investigate the diagnostic and predictive utility of the Cl/P and Cl/Mg ratios in differentiating PHPT subtypes and assessing the risk of osteoporosis and nephrolithiasis. Methods: This retrospective study included 116 patients who underwent parathyroidectomy for PHPT at Ankara Bilkent City Hospital between 2019 and 2022. All patients met surgical criteria based on international guidelines, and normocalcemic PHPT (N-PHPT) cases were defined by repeatedly normal calcium measurements and exclusion of secondary causes. Preoperative biochemical parameters, imaging findings, and complication profiles were analyzed. Cl/P and Cl/Mg ratios were calculated and evaluated using the Mann-Whitney U test, Spearman correlation, and receiver operating characteristic (ROC) analysis. Results: The Cl/P ratio was significantly higher in hypercalcemic PHPT than in normocalcemic patients (median 42.4 vs. 38.3, p=0.0125) and was positively associated with bone mineral density. A Cl/P threshold of >43.6 yielded 80.0% specificity in distinguishing PHPT subtypes [area under the curve (AUC): 64.1%]. The Cl/Mg ratio, although not differing between subtypes, was significantly associated with nephrolithiasis risk, with a cut-off value of ≤55 providing 82.4% sensitivity and 66.7% specificity (AUC: 70.5%, p